Latin America, dependency or interdependence? - Novak, Michael; Jackson, Michael P. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1985)
This book examines the role of multinational corporations in Latin America in the context of social science, theology, existing political realities, and economic developments. its aim is to move from the larger framework of theory towards concrete practices.
Includes bibliographies.
rpm 14/06/2017
Loans
Keywords: Investments, Foreign; Investments, Foreign $1 (BLatin America $1 (BAddresses, essays, lectures.s; Latin America $1 (BEconomic conditions $1 (B1982-s; Latin America $1 (BDependency on foreign countries.s; Latin America $1 (BEconomic conditions $1 (B1945-s; Latin America $1 (BDependency on foreign countries $1 (BAddresses, essays, lectures.s; International economics ; International relations; Latin America